The healing of America - Williamson, Marianne 1952- (Simon & Schuster, 1997)
Noting a spiritually motivated political activism now emerging in America, Marianne Williamson claims that traditional political activists increasingly look to spiritual wisdom for inspiration while spiritual contemplatives are increasingly eager to extend their service to the world into political realms. The convergence of the two impulses forms what Williamson calls a "holistic politics."